Complexity of bidirectional transcription and alternative splicing at human RCAN3 locus. - Federica Facchin (Public Library of Science (PLoS), 2011)
Human RCAN3 (regulator of calcineurin 3) belongs to the human RCAN gene family.In this study we provide, with in silico and in vitro analyses, the first detailed description of the human multi-transcript RCAN3 locus. Its analysis revealed that it is composed of a multigene system that includes at least 21 RCAN3 alternative spliced isoforms (16 of them identified here for the first time) and a new RCAN3 antisense gene (RCAN3AS). In particular, we cloned RCAN3-1,3,4,5 (lacking exon 2), RCAN3-1a,2,3,4,5, RCAN3-1a,3,4,5, RCAN3-1b,2,3,4,5, RCAN3-1c,2,3,4,5, RCAN3-1c,2,4,5 and RCAN3-1c,3,4,5, isoforms that present a different 5' untranslated region when compared to RCAN3. Moreover, in order to verify the possible 5' incompleteness of previously identified cDNA isoforms with the reference exon 1, ten more alternative isoforms were retrieved. Bioinformatic searches allowed us to identify RCAN3AS, which overlaps in part with exon 1a, on the opposite strand, for which four different RCAN3AS isoforms were cloned.In order to analyze the different expression patterns of RCAN3 alternative first exons and of RCAN3AS mRNA isoforms, RT-PCR was performed in 17 human tissues. Finally, analyses of RCAN3 and RCAN3AS genomic sequences were performed to identify possible promoter regions, to examine donor and acceptor splice sequences and to compare evolutionary conservation, in particular of alternative exon 1 or 1c--exon 2 junctions in different species.The description of its number of transcripts, of their expression patterns and of their regulatory regions can be important to clarify the functions of RCAN3 gene in different pathways and cellular processes.